Rational Design, Synthesis, and Biological Evaluation of Lactam‐Bridged Gramicidin A Analogues: Discovery of a Low‐Hemolytic Antibacterial Peptide. Issue 3 (15th December 2014) - Mao, Ji; Kuranaga, Takefumi; Hamamoto, Hiroshi; Sekimizu, Kazuhisa; Inoue, Masayuki
Abstract A linear peptide, gramicidin A (GA), folds into a β6.3‐helix, functions as an ion channel in the cell membrane, and exerts antibacterial activity. Herein we describe the rational design, synthesis, and biological evaluation of lactam‐bridged GA analogues. The GA analogue with a 27‐membered macrolactam was found to adopt a stable β6.3‐helical conformation and exhibits higher ion‐exchange activity than GA. Furthermore, this GA analogue retains the potent antibiotic activity of GA, but its hemolytic activity and toxicity toward mammalian cells are significantly lower than those of GA. This study thus dissociates the antibacterial and hemolytic/cytotoxic activities of GA, and charts a rational path forward for the development of new ion‐channel‐based antibiotics.